Cooperation of LIM domain‐binding 2 (LDB2) with EGR in the pathogenesis of schizophrenia. Issue 4 (3rd March 2021) - Ohnishi, Tetsuo; Kiyama, Yuji; Arima‐Yoshida, Fumiko; Kadota, Mitsutaka; Ichikawa, Tomoe; Yamada, Kazuyuki; Watanabe, Akiko; Ohba, Hisako; Tanaka, Kaori; Nakaya, Akihiro; Horiuchi, Yasue; Iwayama, Yoshimi; et al.
Abstract: Genomic defects with large effect size can help elucidate unknown pathologic architecture of mental disorders. We previously reported on a patient with schizophrenia and a balanced translocation between chromosomes 4 and 13 and found that the breakpoint within chromosome 4 is located near the LDB2 gene. We show here that Ldb2 knockout (KO) mice displayed multiple deficits relevant to mental disorders. In particular, Ldb2 KO mice exhibited deficits in the fear‐conditioning paradigm. Analysis of the amygdala suggested that dysregulation of synaptic activities controlled by the immediate early gene Arc is involved in the phenotypes. We show that LDB2 forms protein complexes with known transcription factors. Consistently, ChIP‐seq analyses indicated that LDB2 binds to > 10, 000 genomic sites in human neurospheres. We found that many of those sites, including the promoter region of ARC, are occupied by EGR transcription factors. Our previous study showed an association of the EGR family genes with schizophrenia. Collectively, the findings suggest that dysregulation in the gene expression controlled by the LDB2‐EGR axis underlies a pathogenesis of subset of mental disorders. Synopsis: The LDB2 gene is mapped in the breakpoint of a balanced chromosomal translocation seen in a patient with schizophrenia. This study provides a role of LDB2 and transcriptional regulation exerted by the "LDB2‐EGR axis" in the pathogenesis of mental disorders. LDB2 forms protein complexes with known transcription regulators such as the LHX and SSBP family proteins. ChIP‐seq analysis identified more than 10, 000 LDB2 binding sites, which contained consensus DNA binding sequence for the EGR family proteins at high proportion. Dysregulation of LDB2 induces modulation in synaptic function via synapse‐related genes such as ARC . A potential role of the "LDB‐EGR axis" in the pathogenesis of mental disorders is suggested. Abstract : The LDB2 gene is mapped at the breakpoint of a balanced chromosomal translocation seen in a patient with schizophrenia. This study investigates the role of LDB2 and transcriptional regulation exerted by the "LDB2‐EGR axis" in the pathogenesis of mental disorders.